Vav3 proto-oncogene deficiency leads to sympathetic hyperactivity and cardiovascular dysfunction - Sauzeau, Vincent (2006)
Although much is known about environmental factors that predispose individuals to hypertension and cardiovascular disease, little information is available regarding the genetic and signaling events involved1-3. Indeed, few genes associated with the progression of these pathologies have been discovered despite intensive research in animal models and human populations1-3. Here we identify Vav3, a GDP-GTP exchange factor that stimulates Rho and Rac GTPases4, as an essential factor regulating the homeostasis of the cardiovascular system.Vav3-deficient mice exhibited tachycardia, systemic arterial hypertension and extensive cardiovascular remodeling. These mice also showed hyperactivity of sympathetic neurons from the time of birth. The high catecholamine levels associated with this condition led to the activation of the renin-angiotensin system, increased levels of kidney-related hormones and the progressive loss of cardiovascular and renal homeostasis. Pharmacological studies with drugs targeting sympathetic and renin-angiotensin responses confirmed the causative role and hierarchy of these events in the development of theVav3-null mouse phenotype. These observations uncover the crucial role of Vav3 in the regulation of the sympathetic nervous system (SNS) and cardiovascular physiology, and reveal a signaling pathway that could be involved in the pathophysiology of human disease states involving tachycardia and sympathetic hyperactivity with unknown etiologies2,5,6.